Maternal Obesity Related to High Fat Diet Induces Placenta Remodeling and Gut Microbiome Shaping That Are Responsible for Fetal Liver Lipid Dysmetabolism - Wang, Ying-Wen; Yu, Hong-Ren; Tiao, Mao-Meng; Tain, You-Lin; Lin, I-Chun; Sheen, Jiunn-Ming; Lin, Yu-Ju; Chang, Kow-Aung; Chen, Chih-Cheng; Tsai, Ching-Chou; Huang, Li-Tung (Frontiers in Nutrition, 2021)
Background: Maternal obesity in utero may affect fetal development and cause metabolic problems during childhood and even adulthood. Diet-induced maternal obesity can impair gut barrier integrity and change the gut microbiome, which may contribute to adverse placental adaptations and increase the obesity risk in offspring. However, the mechanism through which maternal obesity causes offspring metabolic disorder must be identified. Methods: Eight-week-old female rats received a control diet or high-fat (HF) diet for 11 weeks before conception and during gestation. The placentas were collected on gestational day 21 before offspring delivery. Placental tissues, gut microbiome, and short-chain fatty acids of dams and fetal liver tissues were studied. Results: Maternal HF diet and obesity altered the placental structure and metabolism-related transcriptome and decreased G protein–coupled receptor 43 expression. HF diet and obesity also changed the gut microbiome composition and serum propionate level of dams. The fetal liver exhibited steatosis, enhanced oxidative stress, and increased expression of acetyl-CoA carboxylase 1 and lipoprotein lipase with changes in maternal HF diet and obesity. Conclusions: Maternal HF diet and obesity shape gut microbiota and remodel the placenta of dams, resulting in lipid dysmetabolism of the fetal liver, which may ultimately contribute to the programming of offspring obesity.